2017
DOI: 10.21873/anticanres.11337
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1 Inhibits Endoplasmic Reticulum Stress Associated-apoptosis After FoscanPDT Combined with C6-Pyridinium Ceramide or Fenretinide

Abstract: Background/Aim Combining an anticancer agent fenretinide (HPR) or C6-pyridinium ceramide (LCL29) with Foscan-mediated photodynamic therapy (FoscanPDT) is expected to augment anticancer benefits of each substance. We showed that treatment with FoscanPDT+HPR enhanced accumulation of C16-dihydroceramide, and that fumonisin B1 (FB), an inhibitor of ceramide synthase, counteracted caspase-3 activation and colony-forming ability of head and neck squamous cell carcinoma (HNSCC) cells. Because cancer cells appear to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…An outstanding question relates to the mechanism by which DES1 promotes AIS and there are a couple of possibilities. Prior studies have shown that loss of DES1 activity can lead to activation of apoptosis, 66–68 autophagy, 46,67 and ER stress pathways 69 . Our studies here suggest that DES1 is not impacting classical anoikis pathways, as DES1 loss did not induce PARP cleavage or increase caspase activity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…An outstanding question relates to the mechanism by which DES1 promotes AIS and there are a couple of possibilities. Prior studies have shown that loss of DES1 activity can lead to activation of apoptosis, 66–68 autophagy, 46,67 and ER stress pathways 69 . Our studies here suggest that DES1 is not impacting classical anoikis pathways, as DES1 loss did not induce PARP cleavage or increase caspase activity.…”
Section: Discussionsupporting
confidence: 62%
“…Although the DES1 inhibitors used here, namely 4HPR and SKi-II, are known to affect other targets, our conclusions are strongly supported by genetic loss of function experiments as well as gain of function approaches showing that DES1 is sufficient to drive AIS and enhance in vitro tumorigenicity. Of note, although effects of DES1 inhibitors on cell death and proliferation have been reported, [66][67][68] biological consequences of increased DES1 activity and/or expression are less well studied. Furthermore, our studies offer important context as to when DES1 inhibitors could be particularly effective, that is, in the metastatic setting where AIS is a key biology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the induction of apoptosis and autophagy contributed to FB1-induced toxicity [14,[22][23][24][25][26]. We next asked whether the inhibition of ER stress could protect against FB1-induced hepatic apoptosis and autophagy in vivo.…”
Section: Inhibition Of Er Stress By Tudca Inhibits Fb1-induced Hepatimentioning
confidence: 99%
“…Sphingolipids and their ceramide subgroup are building blocks of membranes, but also fulfil numerous other functions in the cell and have been shown to be involved in PDT (95,169). In a series of publications, Korbelik and Separovic (95,96,169,195,(273)(274)(275) analyzed the relevance of sphingolipids for PDT with temoporfin and investigated the synergistic effect of combination therapies, e.g. with the ceramide analogue LCL29, the synthetic retinoide derivative fenretinide and a ceramidase inhibitor.…”
Section: Mechanistic Aspectsmentioning
confidence: 99%